2017
DOI: 10.3892/ijo.2017.3851
|View full text |Cite
|
Sign up to set email alerts
|

miR-148a increases the sensitivity to cisplatin by targeting Rab14 in renal cancer cells

Abstract: MicroRNA (miR) can exert various biological functions by targeting oncogenes or tumor suppressor genes in numerous human malignancies. Recent evidence has shown that miR-148a increases the drug sensitivity of various cancer cells. Herein, we show that ectopic expression of miR-148a induces apoptosis, reduces clonogenicity, and increases the sensitivity to TRAIL and cisplatin in renal cancer cells. The luciferase reporter assay showed that miR-148a negatively regulated ras-related protein 14 (Rab14) expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…As shown in the western blots, RAB14 was a target of miR-338-3p in lung adenocarcinoma cells, and hsa_ circ_0000326 overexpression contributed to elevated levels of RAB14. Alterations in RAB14 expression have been documented in gastric cancer, renal cancer, nasopharyngeal carcinoma and lung cancer [47,51,52]. As an oncogene, RAB14 participates in many biological processes, such as cell proliferation, migration and invasion, by regulating the AKT signaling pathway [51,53].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the western blots, RAB14 was a target of miR-338-3p in lung adenocarcinoma cells, and hsa_ circ_0000326 overexpression contributed to elevated levels of RAB14. Alterations in RAB14 expression have been documented in gastric cancer, renal cancer, nasopharyngeal carcinoma and lung cancer [47,51,52]. As an oncogene, RAB14 participates in many biological processes, such as cell proliferation, migration and invasion, by regulating the AKT signaling pathway [51,53].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the influence of both of these miRNAs has been published widely in other tumor types. miR-130a influences response to chemotherapy in various tumor types such as ovarian cancer 11 , breast cancer 42 and hepatocellular carcinoma 21 , and miR-148a was attributed a central role in drug response in renal 24 and prostate cancer 43 . However, the literature reports partly contradictory results in terms of basal miR-130a expression and intrinsic chemoresistance of various cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of observational studies investigated the prognostic significance of miR-148a in various cancers and reported a correlation between low miR-148a levels and poor overall survival in patients with cancer (6). miR-148a has been found to be dysregulated in several cancers, including ovarian cancer (7), breast cancer (8,9), colorectal cancer (10), gastrointestinal cancer (11), prostate cancer (12), hepatocellular carcinoma (13), papillary thyroid carcinoma (14) and renal cancer (15). In ovarian cancer, miR-148a is decreased in the plasma of patients compared with healthy controls and its expression level is positively associated with survival time (16).…”
Section: Introductionmentioning
confidence: 99%